Optimization Design of the New Type Double Helical Tooth Synchronous Belt and Pulley Structure Parameter - Guo Jianhua; Shao Yue; Hu Qingming; Li Dongsheng; Jiang Hongyuan (Jixie chuandong)
Based on higher order contact meshing theory of conjugate curvature,a three-dimensional model of the new type double helical tooth synchronous belt and the belt drive are established. The nonlinear finite element analysis software is used to analyze the stress and deformation of the new type double helical tooth synchronous belt and the pulley. Through the analysis,the change law of the helix angle,backlash,and pulley structural parameters on the stress and deformation of belt tooth and strength layers is studied,and the structural parameters of the new type double helical tooth synchronous belt with high integrated load carrying capacity are optimized. During laboratory bench fatigue life test,the new type double helical tooth synchronous belt has longer fatigue life than the same tooth profile with straight tooth synchronous belt.